Assessing Integrated Farming System Models Apropos Employment Generation Potential in Madhya Pradesh (Indian Journal of Extension Education, 2019)
Integrated Farming System (IFS) approach has been identified as the way-out for providing income and employment to the millions farmers and farm women engaged in agriculture sector. It has immense potential to ensure livelihood as well as income security to the persons engaged through any component of IFS. The study was conducted in Mandla district of Madhya Pradesh to assess the IFS models in relation to employment generation of tribal farmers. The study was conducted with 250 respondents (125 respondents each from marginal and small land holdings respondents) selected randomly from 5 blocks using personal interview. Results revealed that, among the 10 IFS models in study area high employment generation was found in the category of Crop + dairy (1816 man days/year) followed by Crop + dairy + poultry (533 man days/year), Crop + dairy + goat rearing (202 man days/year), Crop + dairy + poultry + goat rearing (64 man days/year), Crop + poultry (61 man days/year), Crop + dairy + fishery (41 man days/years), Crop + poultry + Goat rearing (27 man days/year), Crop + Dairy + Goat rearing + Fishery (20 man days/year), Crop + fishery (18 man days/year) and very least in case of Crop + Goat rearing (11 man days/year). Correlation analysis reveals that out of 18 independent variables only 6 variables were significantly correlated with employment generation by IFS either at 0.05 or at 0.01 level of probability.